2020
DOI: 10.1039/d0na00247j
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube columns for flow systems: influence of synthesis parameters

Abstract: Carbon nanotube columns are ideal simple scaffolds to develop various flow systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…It encouraged CNT length and yield as a whole. Since these carriers or protective gases (at least the first three) were considered inert and unreactive in the formation of CNTs, this was not previously anticipated [97]. In a similar study by Quinson et al on the effect of carrier gas flow rate, it was discovered that a flow rate of 2500 sccm is preferable to values of 1000 or 5000 sccm for producing homogeneous, vertically aligned MWCNTs [98].…”
Section: Carrier Gasesmentioning
confidence: 93%
See 1 more Smart Citation
“…It encouraged CNT length and yield as a whole. Since these carriers or protective gases (at least the first three) were considered inert and unreactive in the formation of CNTs, this was not previously anticipated [97]. In a similar study by Quinson et al on the effect of carrier gas flow rate, it was discovered that a flow rate of 2500 sccm is preferable to values of 1000 or 5000 sccm for producing homogeneous, vertically aligned MWCNTs [98].…”
Section: Carrier Gasesmentioning
confidence: 93%
“…Another critical factor in the formation of CNTs is the carrier gas and the flow rate; to promote the development of fine nanotubes, a low catalyst concentration, and a high carrier gas flow rate could be necessary. The formation of CNTs has been seen to be influenced by a variety of carrier gases, including nitrogen (N 2 ), argon (Ar), ammonia (NH 3 ), helium (He), and hydrogen (H 2 ) [97]. A study by Panahi et al on the effects of different carrier gases observed that diatomic nitrogen (N 2 ) performed better when evaluated as a carrier gas for CNT formation of CNTs, outperforming the other three (N 2 , Ar, He, and CO 2 ).…”
Section: Carrier Gasesmentioning
confidence: 99%